Construct validity of the resistance training skills battery in children aged 7-10 years. Issue 17 (2nd September 2018) - Duncan, Michael J.; Lawson, Chelsey; Hurst, Josh; Tallis, Jason; Jones, Victoria; Eyre, Emma L. J.
ABSTRACT: The current study sought to examine the construct validity of the Resistance Training Skills Battery for Children (RTSBc), a movement screen purported to assess resistance training skill in children. Children aged 7–10 years (n = 27, 21 males, 6 females) undertook measures of resistance training skill via the RTSBc, motor competence and muscular fitness. Using a median split for RTSBc scores, children were categorised as high or low resistance training competence. Univariate ANCOVAs, controlling for maturation, were used to examine whether measures of muscular fitness and motor competence scores differed as a function of RTSBc competence. Children who were classified as high for resistance training competence had significantly better motor competence (P = .001) and significantly faster 10 m sprint speed (P = .001). However, medicine ball throw and standing long jump scores as well as peak and average isokinetic muscle strength did not differ as a function of RTSBc (P > 0.05). In all cases maturation was significant as a covariate. This study is the first to demonstrate construct validity of the RTSBc as a measure of general motor competence and sprint speed, but not strength, in children aged 7–10 years.